Examining the determinants of users' acceptance of IT in the Yemeni public sector: pilot study - Wahdain, Esmat Abdulmajeed; Ahmed, Mohammad Nazir (2015)
This paper presents the results of a pilot study conducted to test a pre-proposed model. The model modified the technology acceptance model (TAM) by adding the constructs: Organizational culture, Individual factors, Gender, and Perceived Personal Benefit to the original version of TAM. Data was collected quantitatively from30 employees of the Ministry of Social Affairs and Labor (MoSAL) Yemen, whom their jobs involve using IT. SmartPLS software PLS-SEM method was used to test the reliability of measurement model, and to assess the structural model. The results confirmed the reliability of the research instrument, as the measures of internal consistency were mostly acceptable. The results also indicated the significance of the hypotheses that relates organizational culture with perceived usefulness and perceived personal benefit; the. Finally, the model showed a good predictive power since 47% of the focal factor, behavioral intention, was explained by its relationships with the other factors.